The Effect of NPM, NPF, DAR, CIR, and DPK on Profitability (ROA) of Islamic Banks in the World - Dewi, Annisa Sinta; Wardana, Guntur Kusuma; Yuliana, Indah (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
In banks, the aspect that is able to show profit conditions is called profitability. There are other aspects that can affect profitability such as NPM, NPF, DAR, CIR, and also DPK. This study aims to determine the effect of NPM, NPF, DAR, CIR, and DPK on the profitability of Islamic banks in the world. This research uses quantitative methods. ers The population in this study were 100 Islamic banks listed as The Strongest Islamic Bank In The World according to The Asian banker using purposive sampling technique which resulted in 20 samples. The data in this research is secondary data taken from the annual reports of each Islamic bank for the 2019-2023 period. The results showed that the variables NPM and CIR each partially had a significant effect on the profitability of Islamic banks in the world. Meanwhile, the NPF, DAR, and DPK variables each show results that have no significant effect on the profitability of Islamic banks in the world. Simultaneously, NPM, NPF, DAR, CIR, and DPK have a significant effect on the profitability of Islamic banks in the world.